Pengaruh tingkat literasi keuangan, experienced regret, dan risk tolerance pada pemilihan jenis investasi - I Putu Santika Putra; Herliana Ananingtiyas; Dea Rachmalita Sari; Aninda Sandra Dewi; Mellyza Silvy (Journal of Business & Banking, 2015)
Nowadays, the economy has been growing so rapidly that it makes people think of get-ting their income beyond the salary they get from their work. One way to get it is by investing. However, when investing, they find a few things to note such as financial literacy, investment experience, and risk tolerance. This is to minimize the risks as we accept, for example scams. This purpose of study is to examine the effect of financial lite-racy, experienced regret, and risk tolerance on investment decision making among socie-ty in Surabaya and Madura. This study used purposive, convenience and snow-ball sampling method. There were 185 respondents taken by questionnaire and survey me-thod. To test the hypotheses, this study employed descriptive analysis and multiple re-gression analysis. Moreover, by performing multiple regression analysis, this study found that only the experienced regret have significant effect on investment decision making, but risk tolerance and overconfidence did not affect the investment decision.